2017
DOI: 10.1136/sextrans-2017-053193
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health clinic attendance and non-attendance in Britain: findings from the third National Survey of Sexual Attitudes and Lifestyles (Natsal-3)

Abstract: ObjectivesIn Britain, sexual health clinics (SHCs) are the most common location for STI diagnosis but many people with STI risk behaviours do not attend. We estimate prevalence of SHC attendance and how this varies by sociodemographic and behavioural factors (including unsafe sex) and describe hypothetical service preferences for those reporting unsafe sex.MethodsComplex survey analyses of data from Britain’s third National Survey of Sexual Attitudes and Lifestyles, a probability survey of 15 162 people aged 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 17 publications
1
46
0
1
Order By: Relevance
“…The fact that individuals rarely have complete information on these factors, combined with other influences on risk perception as described above may lead to an under- or over-estimation of individual STI risk, which in turn could influence sexual behaviour and healthcare-seeking. We have previously shown that in Britain, substantial proportions of those at risk had not accessed sexual health clinics or chlamydia testing despite these services being free at the point of care [8] , suggesting either a lack of risk perception or other barriers to accessing care. We have also previously shown a mismatch between HIV risk perception and indicators of HIV risk among the British population [9] , however these findings may not be generalisable to other STIs due to real and perceived differences in how prevalent the infections are, which population groups are affected, and the consequences of infection.…”
Section: Introductionmentioning
confidence: 98%
“…The fact that individuals rarely have complete information on these factors, combined with other influences on risk perception as described above may lead to an under- or over-estimation of individual STI risk, which in turn could influence sexual behaviour and healthcare-seeking. We have previously shown that in Britain, substantial proportions of those at risk had not accessed sexual health clinics or chlamydia testing despite these services being free at the point of care [8] , suggesting either a lack of risk perception or other barriers to accessing care. We have also previously shown a mismatch between HIV risk perception and indicators of HIV risk among the British population [9] , however these findings may not be generalisable to other STIs due to real and perceived differences in how prevalent the infections are, which population groups are affected, and the consequences of infection.…”
Section: Introductionmentioning
confidence: 98%
“…In terms of services, participants’ accounts indicated virtual absence of GP-initiated discussion of sexual matters and a perception of specialist sexual health services as youth-focused. Previous research suggests preference for STI diagnosis and treatment in general practice among at-risk individuals not attending sexual health clinics 29. GP training may, therefore, be useful to challenge assumptions about the sex lives of midlife patients and equip them with confidence to raise discussions.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are somewhat more difficult to interpret than those of nationally representative surveys, 23 25 because ethnic and gender differences may be diluted among the high-risk population of SHC attendees. 25 26 However, we used a clinic-verified outcome, in conjunction with detailed patient-reported data.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%